Collagen membranes at immediate implants: a histomorphometric study in dogs - Caneva, Marco [UNESP]; Botticelli, Daniele [UNESP]; Salata, Luiz Antonio; Scombatti Souza, Sergio Luis; Cardoso, Leandro Carvalho; Lang, Niklaus Peter (Wiley-Blackwell, 2010)
AimTo evaluate the influence of resorbable membranes on hard tissue alterations and osseointegration at implants placed into extraction sockets in a dog model.Material and methodsIn the mandibular premolar region, implants were installed immediately into the extraction sockets of six Labrador dogs. Collagen-resorbable membranes were placed at the test sites, while the control sites were left uncovered. Implants were intended to heal in a submerged mode. After 4 months of healing, the animals were sacrificed, and ground sections were obtained for histomorphometric evaluation.ResultsAfter 4 months of healing, a control implant was not integrated (n=5). Both at the test and at the control sites, bone resorption occurred. While the most coronal bone-to-implant contact was similar between the test and the control sites, the alveolar bone crest outline was maintained to a higher degree at the buccal aspect of the test sites (loss: 1.7 mm) compared with the control sites (loss: 2.2 mm).ConclusionsThe use of collagen-resorbable membranes at implants immediately placed into extraction sockets contributed to a partial (23%) preservation of the buccal outline of the alveolar process.To cite this article:Caneva M, Botticelli D, Salata LA, Souza SLS, Carvalho Cardoso L, Lang NP. Collagen membranes at immediate implants: a histomorphometric study in dogs.Clin. Oral Impl. Res. 21, 2010; 891-897.doi: 10.1111/j.1600-0501.2010.01946.x.
Keywords: animal study; bone healing; collagen membrane; extraction socket; implant dentistry; osseointegration; regeneration; ridge preservation